The AGM in Europe : theory and practice of shareholder behaviour - Lafarre, Anne (Emerald Publishing Limited, 2017)
Business, Economics and Legal scholars have all argued about the theoretical importance of annual general meetings in assessing business shareholder relations and wider issues of corporate governance, but often without knowing how the AGM functions in practice. Anne Lafarre combines wide ranging empirical legal and economic research to analyse and understand the real role of the AGM in the European businesses and corporate governance frameworks today. Focusing on seven European member states (Austria, Belgium, France, Germany, Ireland, the Netherlands and the UK) the author persuasively explores how the impact of legal rulings and business pressures effects shareholder representation in European AGMs and their propensity to affect change through these forums. Drawing wide ranging data sets to challenge existing economic and legal theory, the author presents practical conclusions and future policy implications.